Ecological multidimensional retention system for rainwater drainage on bank side of river - ZHANG ZHIGANG; GAO CHAO; SUN JINGMEI; TANG YINQI (2015)
The invention discloses an ecological multidimensional retention system for rainwater drainage on a bank side of a river. A primary ecological buffer zone, a first-layer ecological retention system, a second-layer ecological retention system, a third-layer ecological retention system and a secondary ecological buffer zone are orderly arranged on the upstream side of a river embankment along the slope of the bank side; the three layers of ecological retention systems are in concentric semi-annular radial form and of ditch type structures; each ecological retention system is provided with a planting soil layer, a packing layer and a gravel layer, and plants good in stress resistance and prosperous in root system are planted on the ecological retention system; herbaceous plants are planted in the two ecological buffer zones. The ecological multidimensional retention system is capable of reducing the pollution load due to the fact that rainwater runoff is directly discharged into receiving water by use of the retention spaces; due to closure and adsorption by use of a filter material and purification of rainwater runoff pollution by use of the plant root system, partial heavy metal ions, pathogens and the like can be removed; the ecological multidimensional retention system is suitable for any rainwater volume and water quality and has a good landscape effect.